The Impact of Using an Enrichment Program Based on Cognitive Control on the Depth of Mathematical Knowledge Among Female High Achievers Students in Mathematics - Al-Azzawi, Safa; Faris , Ilham (Al-Adab Journal, 2025)
The current research aims to:Construct an enrichment program according to the strength of cognitive control for outstanding female students in the first intermediate grade.Knowing the impact of the enrichment program on the cognitive depth of outstanding female students in the first intermediate year.   To achieve these objectives, an experimental research method was adopted. The research population consisted of first-year intermediate-level female students enrolled in schools for gifted students under the directorates of education in Rusafa 1, 2, and 3 in Baghdad Governorate for the academic year 2023-2024. The total number of day study intermediate schools was 6, and the total research population was 642 female students. The experiment was applied to a sample consisting of 54 female students, including an experimental group of 28 students and a control group of 26 students. These students were selected from the first-year intermediate level at the first school for gifted female students under the Rusafa 2 education directorate in Baghdad for the academic year 2023-2024. Both groups were equated on variables such as prior mathematics knowledge, chronological age, previous achievement, prior knowledge, intelligence, and parents' educational level.An enrichment program based on cognitive control was developed, covering three chapters from the first-year intermediate-level mathematics textbook (chapters 5, 6, and 7). A test was constructed to assess different levels of mathematical knowledge (recall and reproduction, application of concepts and skills, strategic thinking, and extended thinking). The test consisted of 42 multiple-choice items, distributed as follows: 17 items for recall and reproduction, 12 items for application of concepts and skills, 4 items for strategic thinking, and 9 items for extended thinking. The test's validity and reliability were established. The experimental group was taught using the traditional method in addition to the enrichment program, while the control group was taught using the traditional method only. After the experiment, the depth of mathematical knowledge test was administered to both groups. Using appropriate statistical analysis, the results showed that the experimental group significantly outperformed the control group in terms of the depth of mathematical knowledge.